Comparison of New and Previous Net Energy Metering (NEM) Scheme in Malaysia - Razali, Abdul Hafiz; Abdullah, Md Pauzi; Hassan, Mohammad Yusri; Hussin, Faridah (ELEKTRIKA- Journal of Electrical Engineering, 2019)
The introduction of new Net Energy Metering (NEM) scheme in 2016 in Malaysia is seen as an improvement from the previous FIT scheme. NEM allows a user to generate, use and export the net excess energy to the grid instead of selling all the generated energy as in FIT scheme. However, the NEM scheme (NEM 2016) still have a problem which is small size residential customers will not get benefited from the scheme in term of electricity bill savings. Therefore, the Malaysian government introducing a new NEM scheme (NEM 2019) to replace previous NEM scheme (NEM 2016) to overcome drawbacks of NEM 2016. This paper will investigate the performance of NEM 2019 overcome the previous problem by comparing the performance of NEM 2019 and against NEM 2016 in term of NPC (net present cost) and electricity cost savings by using HOMER software. The analysis is conducted on three different size of residential customers; small, medium and large with different PV panel sizes from 1kWp to 8kWp. The results show that NEM 2019 will produce lower NPC compared to NEM 2016 for most cases.